163 Long-term safety of adjunctive cenobamate in patients with uncontrolled focal seizures. Issue 6 (27th May 2022) - Morales, Irene Garcia; Brodie, Martin J; Milanov, Ivan; Czlonkowska, Anna; Brandt, Christian; lan, Lee Fin-; Alvarez-Baron, Elena; Steinhoff, Bernhard J
Abstract : Purpose: Results from two double-blind, placebo-controlled studies demonstrated that adjunctive ceno- bamate significantly reduced the frequency of seizures vs placebo. Cenobamate 200mg/day achieved seizure freedom in 28.3% vs 8.8% placebo (P<0.0003; 013 study maintenance phase) and 21.1%, 11.2% for cenobamate 400mg/d and 200mg/d, respectively, vs 1% in placebo (P<0.002; 017 maintenance phase). Cenobamate also showed a favorable safety and tolerability profile. Here, we report the combined long-term safety and tolerability outcomes from the ongoing open-label extensions (OLEs) of C013 and C017. Methods: Adults with uncontrolled FOS were enrolled in two double-blind, placebo-controlled studies. Patients completing both double-blinded phases were invited to participate in OLE studies (n=504). Results: As of July 2019, 58.3% of the patients who entered the OLEs, continued; at baseline, median age was 38 years, and 86.5% were taking ≥2 concomitant AEDs. Median (range) length of exposure was 237 weeks (1–407). The most frequent TEAEs (≥10%) were dizziness (33.9%), somnolence (23.6%), headache (18.7%), fatigue (14.3%), diplopia (12.9%) and upper respiratory tract infections (12.3%). Most TEAEs were mild or moderate (78%). 22% experienced SAEs of which only seizure exceeded 1% (n=11). Discontinu- ations were due to TEAE (8%), withdrawal by patient (12%), lack of efficacy (12%), other (4%). No cases of DRESS were reported. Conclusions: Long-term adjunctive cenobamate treatment (up to 94 months) is generally well tolerated. Most TEAEs were CNS-related and consistent with those shown in the two double-blind studies. lee.finlan@arvelletx.com